Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/03043797.2014.899323
|View full text |Cite
|
Sign up to set email alerts
|

Paving the way and passing the torch: mentors’ motivation and experience of supporting women in optical engineering

Abstract: The phenomenon of women's underrepresentation in engineering is well known. However, the slow progress in achieving better gender equality here compared with other domains has accentuated the 'numbers' issue, while the quality aspects have been largely ignored. This study aims to shed light on both these aspects via the lens of mentors, who are at the coalface of guiding female engineers through their education and subsequent careers. Based on data collected from 25 mentors (8 men and 17 women from 8 countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some other researcher have also shown that the situation that prevent women from finding or even seeking employment in TVE fields is as a result of few women role models who could inform women students about opportunities in these fields (Samulewicz et al, 2012). A study by Kodate et al, (2014) underscores the need for invigorating mentors' role in order to secure a more equitable future for women in technical and vocational education. Institutions and government of Nigeria have to consider implementing not only formal mentoring program but also providing forums for informal mentoring programs.…”
Section: Discussionmentioning
confidence: 99%
“…Some other researcher have also shown that the situation that prevent women from finding or even seeking employment in TVE fields is as a result of few women role models who could inform women students about opportunities in these fields (Samulewicz et al, 2012). A study by Kodate et al, (2014) underscores the need for invigorating mentors' role in order to secure a more equitable future for women in technical and vocational education. Institutions and government of Nigeria have to consider implementing not only formal mentoring program but also providing forums for informal mentoring programs.…”
Section: Discussionmentioning
confidence: 99%
“…Given how little is known about civilian employees in policing-and dispatchers specifically-our study demonstrates the police subculture can be applied along a variety of dimensions. Traditionally, the "us versus them" component of police culture is oriented outward; in other words, it is used to describe how police view those outside of the department (researchers, politicians, others in the criminal justice system and even the general public; Kodate et al, 2014;Boivin et al, 2020;Phillips, 2020). Some research has also applied it internally, either in a vertical orientation (i.e.…”
Section: Scholarly and Theoretical Implicationsmentioning
confidence: 99%